Factors Affecting The Use Of BNI Mobile Banking In Tasikmalaya - Nugraha, Cindera Syaiful; Sakifah, Sakifah; Subrata, Ali (Jurnal Ekonomi, 2024)
M-banking is an electronic banking service that benefits not only customers but also the providing bank. The purpose of this research is to identify and analyze the factors influencing the use of BNI M-Banking by customers of BNI Bank, Tasikmalaya Branch. These factors are categorized into customer characteristics (gender, age, occupation, education) and perception factors (ease of use, usefulness, convenience, availability of features). This research employs a quantitative approach with an explanatory method. Data collection is conducted through questionnaires and literature studies. To determine the influence of customer characteristics on the use of BNI Mobile Banking, the Chi-square test technique is used. Multiple linear regression analysis is used to determine the influence of customer perception factors. The results show that ease of use, usefulness, and availability of features have a significant positive influence on user interest, whereas convenience does not significantly affect user interest.